Sustaining the mass Cocoa spraying program in the Ahafo Ano North District in Ashanti - Suglo, Joseph (2015)
A thesis submitted to the School of Graduate Studies, Kwame Nkrumah University of Science and Technology, in partial fulfillment of the requirement for the degree of MASTER OF SCIENCE DEVELOPMENT POLICY AND PLANNING. 2012